Utilization of Information and Communication Technology in an Effort to Improve the Effectiveness of Learning Management and Address Process Issues Developing Teaching Skills during the Covid-19 Pandemic : A Literature Study - Iskandar Ahmaddien; Nurhayati Nurhayati; Deny Purwo Sambodo; Fitria Lilyana (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to gain an understanding of how information and communication technology can be used to improve the effectiveness of learning management in the era of the covid-19 pandemic, as well as to determine the challenges that teachers and students face during this distance learning process, as well as the solutions that are provided. This research took the strategy of doing a literature review. The results of the study show that from 10 previous studies both national and international, good learning management is the main key to implementing effective learning. To ensure the quality of learning, educators as much as possible manage learning starting from planning, organizing, actuating and evaluating. In learning management in this pandemic era, the application of information and communication technologies is one of the efforts to increase the effectiveness of the learning process. Various applications that can help the learning process in the world of education such as zoom applications, google classroom, whatsapp and several technological media that can be utilized. In the process of homework and assessments the teacher can also provide an assessment that is in accordance with the competence of students with the help of several applications such as kahoot, google form, quizizz and other applications. However, all of this cannot be separated from the challenges and obstacles in carrying out online learning. Lack of technological facilities, understanding of information and communication technologies from both the teacher and students makes learning less than optimal. Therefore, this progress must be followed by the development of educator resources. It is necessary to have ICT infrastructure in place to facilitate this development. It is vital for educators to be taught in information and communications technology (ICT) since ICT can be utilized to aid with administrative tasks. ICT can be utilized to assist in the packaging of educational materials (Multimedia) to meet the demands of students. The use of information and communications technology (ICT) can aid in the learning management process (E-learning, advanced requirements). Technical assistance and knowledge expansion can be achieved through the use of information and communications technology (ICT). When instructors and students have a strong grasp of the material, they will be able to boost the efficacy and efficiency of the learning process, resulting in optimal outcomes. The use of information and communication technology is not only limited to activities to convey information but can also be used to create learning interactions. The use of online social media is used for interaction, discussion between students, or students with teachers. The use of e-learning as a learning process by utilizing computers and the internet must also be developed for teachers and students. discussion between students, or students with teachers.